The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5051/jpis.2013.43.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic effect of blue light on the planktonic and biofilm state of anaerobic periodontal pathogens

Abstract: PurposeThe purpose of this study was to compare the phototoxic effects of blue light exposure on periodontal pathogens in both planktonic and biofilm cultures.MethodsStrains of Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, and Porphyromonas gingivalis, in planktonic or biofilm states, were exposed to visible light at wavelengths of 400.520 nm. A quartz-tungsten-halogen lamp at a power density of 500 mW/cm2 was used for the light source. Each sample was exposed to 15, 30, 60, 90, or 120 second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(39 reference statements)
3
41
0
Order By: Relevance
“…It is supported by in vitro studies that report effective killing of periodontal microbes in planktonic and biofilm samples. 16,17 Therefore, the aim of the present study was to evaluate the additional benefit of aPDT, if any, in addition to SRP alone. At the baseline examination, there was no statistically significant difference between the two groups in any of the recorded parameters i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is supported by in vitro studies that report effective killing of periodontal microbes in planktonic and biofilm samples. 16,17 Therefore, the aim of the present study was to evaluate the additional benefit of aPDT, if any, in addition to SRP alone. At the baseline examination, there was no statistically significant difference between the two groups in any of the recorded parameters i.e.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that increases in temperature could damage bacteria after exposure to blue light. Oxidative stress occurs with reactive oxygen species such as superoxide anion, hydrogen peroxide, and hydroxyl radicals that damage proteins, DNA, lipid, and the cell membrane 32 .Hyun-Hwa Song et al (2013) showed that blue light exposure is available to reduce periodontal pathogens in the planktonic state. However, periodontal pathogens in the intraoral environment exist in a biofilm state.…”
Section: Discussionmentioning
confidence: 99%
“…And found a Little phototoxic effect even in the biofilm states of A. actinomycetemcomitans and F. nucleatum. Therefore he recommended that an adjunctive exogenous photosensitizer (e.g., methylene blue, toluidine blue O, erythrosine) be used when visible light exposure is used for antimicrobial periodontal therapy 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27,28 Other studies demonstrated that aBL did not cause significant damages to host cells and did not impair wound healing. 18,26,28,34,39,40 In this issue of Virulence, Fila et al 22 investigated the effectiveness of aBL inactivation of Pseudomonas aeruginosa using a panel of wide types and clinical strains, including multidrug-resistant and extensively drug-resistant strains. In agreement of previous studies, the authors found that aBL exerted significant antimicrobial effect on all Pseudomonas aeruginosa strains tested, resulting in 5.2-to 8-log 10 reduction of colony forming units (CFU).…”
mentioning
confidence: 99%